Agricultural drought propagation across major sorghum growing districts in Tamil Nadu, India - Manikandan, N; Geethalakshmi, V; Santanu, Kumar Bal; Sathyamoorthy, N K; Balaji, Kannan; Ravikumar, R (Plant Science Today, 2025)
Quantifying the response time between meteorological and agricultural drought is vital to understanding the drought evolution and to improve monitoring. The present investigation used the % of normal precipitation and the soil moisture deficit index at a weekly scale to know spatial variations in the frequency of meteorological and agricultural drought and propagation time between these droughts in major sorghum growing districts of Tamil Nadu state. Results showed that the frequency of extreme meteorological drought was 34-68 % and 40-55 % in the first and second sorghum growing seasons, respectively. However, moderate and severe dry conditions occurred for 1-2 weeks in both seasons. In case of agricultural drought, the highest moderate drought frequency (50 %) was noticed in Ramanathapuram and Thoothukudi districts during the first season and in Coimbatore and Thoothukudi districts in the second season. The shortest drought response time of 4-5 weeks was seen in western, southern and central parts of the state, while north-western and north-eastern districts showed the longest response time of 17-18 weeks. The shorter transition time in western, southern and central regions could be attributed to low seasonal rainfall, higher frequency of extreme dry conditions during the first growing season and the presence of fine textured black and brown soils with shallow rooting depth These districts require careful planning and quick interventions to curtail the agricultural drought impact, as regional and global climatic models projected a rise in occurrence and severity of drought events in the coming year.